ART in Europe, 2015: results generated from European registries by ESHRE. Issue 1 (24th February 2020) - De Geyter, C; Calhaz-Jorge, C; Kupka, M S; Wyns, C; Mocanu, E; Motrenko, T; Scaravelli, G; Smeenk, J; Vidakovic, S; Goossens, V; ,
Abstract: STUDY QUESTION: What are the European trends and developments in ART and IUI in 2015 as compared to previous years? SUMMARY ANSWER: The 19th ESHRE report on ART shows a continuing expansion of treatment numbers in Europe, and this increase, the variability in treatment modalities and the rising contribution to the birth rates in most participating countries all point towards the increasing impact of ART on European society. WHAT IS KNOWN ALREADY: Since 1997, the ART data generated by national registries have been collected, analysed and reported in 18 manuscripts published in Human Reproduction. STUDY DESIGN, SIZE, DURATION: Collection of European data by the European IVF-Monitoring Consortium (EIM) for ESHRE. The data for treatments performed between 1 January and 31 December 2015 in 38 European countries were provided by national registries or on a voluntary basis by clinics or professional societies. PARTICIPANTS/MATERIALS, SETTINGS, METHODS: From 1343 institutions in 38 countries offering ART services a total of 849 811 treatment cycles, involving 155 960 with IVF, 385676 with ICSI, 218098 with frozen embryo replacement (FER), 21 041 with preimplantation genetic testing (PGT), 64 477 with egg donation (ED), 265 with IVM and 4294 with FOR were recorded. European data on IUI using husband/partner's semen (IUI-H) and donor semen (IUI-D) were reported from 1352 institutions offering IUI in 25 countries and 21 countries, respectively. A total of 139 050 treatments with IUI-H and 49 001 treatments with IUI-D were included. MAIN RESULTS AND THE ROLE OF CHANCE: In 18 countries (14 in 2014) with a population of approximately 286 million inhabitants, in which all institutions contributed to their respective national registers, a total of 409 771 treatment cycles were performed, corresponding to 1432 cycles per million inhabitants (range: 727–3068 per million). After IVF the clinical pregnancy rates (PRs) per aspiration and per transfer were slightly lower in 2015 as compared to 2014, at 28.5 and 34.6% versus 29.9 and 35.8%, respectively. After ICSI, the corresponding PR achieved per aspiration and per transfer in 2015 were also slightly lower than those achieved in 2014 (26.2 and 33.2% versus 28.4 and 35.0%, respectively). On the other hand, after FER with own embryos the PR per thawing continued to rise from 27.6% in 2014 to 29.2% in 2015. After ED a slightly lower PR per embryo transfer was achieved: 49.6% per fresh transfer (50.3% in 2014) and 43.4% for FOR (48.7% in 2014). The delivery rates (DRs) after IUI remained stable at 7.8% after IUI-H (8.5% in 2014) and at 12.0% after IUI-D (11.6% in 2014). In IVF and ICSI together, 1, 2, 3 and ≥4 embryos were transferred in 37.7, 53.9, 7.9 and in 0.5% of all treatments, respectively (corresponding to 34.9, 54.5, 9.9 and in 0.7% in 2014). This evolution towards the transfer of fewer embryos in both IVF and ICSI resulted in a proportion of singleton, twin and triplet DR of 83.1, 16.5 and 0.4%, respectively (compared to 82.5, 17.0 and 0.5%, respectively, in 2014). Treatments with FER in 2015 resulted in twin and triplet DR of 12.3 and 0.3%, respectively (versus 12.4 and 0.3% in 2014). Twin and triplet delivery rates after IUI-H were 8.9 and 0.5%, respectively (in 2014: 9.5 and 0.3%), and 7.3 and 0.6% after IUI-D (in 2014: 7.7 and 0.3%). LIMITATIONS, REASONS FOR CAUTION: The methods of data collection and reporting vary among European countries. The EIM receives aggregated data from various countries with variable levels of completeness. Registries from a number of countries have failed to provide adequate data about the number of initiated cycles and deliveries. As long as incomplete data are provided, the results should be interpreted with caution. WIDER IMPLICATIONS OF THE FINDINGS: The 19th EIM report on ART shows a continuing expansion of treatment numbers in Europe. The number of treatments reported, the variability in treatment modalities and the rising contribution to the birth rates in most participating countries point towards the increasing impact of ART on reproduction in Europe. Being the largest data collection on ART worldwide, detailed information about ongoing developments in the field is provided. STUDY FUNDING/COMPETING INTEREST(S): The study has no external funding and all costs are covered by ESHRE. There are no competing interests.